2000
DOI: 10.1016/s0886-3350(00)00748-3
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of fibronectin, vitronectin, laminin, and collagen type IV to intraocular lens materials in pseudophakic human autopsy eyes

Abstract: This study seems to confirm the sandwich theory of posterior capsule opacification in eyes with an IOL and suggests that fibronectin may be the major extracellular protein responsible for the attachment of hydrophobic soft acrylate (AcrySof(R)) IOLs to the capsular bag. This may represent a true bioactive bond between the IOL and lens epithelial cells or between the IOL and the capsular bag and may be one reason the PCO and neodymium:YAG capsulotomy rates are lower in eyes with a soft acrylate IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
114
1
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(126 citation statements)
references
References 36 publications
5
114
1
6
Order By: Relevance
“…There is preliminary evidence that the Alcon AcrySof  IOL biomaterial provides such enhanced adhesion, or 'bioadhesion'. 90,91 This will require further study. (3) Barrier effect of the IOL optic: The IOL optic barrier effect plays an important role as a second line of defense against PCO, especially in cases where retained cortex and cells remain following ECCE ('no space, no cells').…”
Section: Three Iol-related Factors To Reduce Pcomentioning
confidence: 99%
“…There is preliminary evidence that the Alcon AcrySof  IOL biomaterial provides such enhanced adhesion, or 'bioadhesion'. 90,91 This will require further study. (3) Barrier effect of the IOL optic: The IOL optic barrier effect plays an important role as a second line of defense against PCO, especially in cases where retained cortex and cells remain following ECCE ('no space, no cells').…”
Section: Three Iol-related Factors To Reduce Pcomentioning
confidence: 99%
“…Literature reports suggest that this material is associated with a lower degree of PCO formation. 29,30 A few authors 31 found that in patients older than 60 years the rate of PCO formation was significantly lower in patients with DM and with an acrylic PC IOL than in patients without DM with a silicone foldable PC IOL. In contrast, within groups A and B, in eyes with partial anterior capsule overlap on the IOL optic there was a higher level of development of PCO, with a significant difference when compared with eyes with total anterior capsule overlap on the IOL optic.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been reported that the optic material of the AcrySof IOL tends to readily absorb intensely adhesive proteins, including fibronectin and vitronectin, which may lead to a strong adhesion of the optic to the lens capsule, and to subsequent prevention of PCO. [27][28][29][30] Surface whitening, which is known to often occur around the AcrySof optic, 31 is supposed to consist of these proteins or water. On the other hand, the optic surface of the Sensar IOL seems to be smoother than that of the AcrySof IOL, because the Sensar IOL is made using cryo lathe cut and tumble polish methods, whereas the AcrySof IOL is made using cast moulding method.…”
Section: Discussionmentioning
confidence: 99%